2021
DOI: 10.3389/fpsyg.2021.737916
|View full text |Cite
|
Sign up to set email alerts
|

Facial Prominence of Political Candidates: Gender Differences in Private and Public Pages on Facebook Profile

Abstract: The face of a person is an important source of communication and information especially for politicians who are continuously portrayed through media. Voters may use this information to form an impression about the candidates and several inferences may be drawn. Within this frame, research has largely investigated gender differences. One line of research has focused on the facial prominence of people portrayed in pictures, describing a tendency to portray men with a higher face prominence as compared to women. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Several recommendations for future research are suggested: First, investigating other social media platforms, such as Instagram, would provide a more comprehensive understanding of how women’s experiences of violence are represented across different digital spaces. Each platform has its unique features, audience, and communication style, which could impact the portrayal of women (Limniou et al, 2022; Roberts & David, 2023; Valmori et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Several recommendations for future research are suggested: First, investigating other social media platforms, such as Instagram, would provide a more comprehensive understanding of how women’s experiences of violence are represented across different digital spaces. Each platform has its unique features, audience, and communication style, which could impact the portrayal of women (Limniou et al, 2022; Roberts & David, 2023; Valmori et al, 2021).…”
Section: Discussionmentioning
confidence: 99%